2008
DOI: 10.1136/bmj.a2396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of algorithm for diagnosis of active labour: cluster randomised trial

Abstract: Objective To compare the effectiveness of an algorithm for diagnosis of active labour in primiparous women with standard care in terms of maternal and neonatal outcomes.Design Cluster randomised trial.Setting Maternity units in Scotland with at least 800 annual births.Participants 4503 women giving birth for the first time, in 14 maternity units. Seven experimental clusters collected data from a baseline sample of 1029 women and a post-implementation sample of 896 women. The seven control clusters had a baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…The present study shows a higher percentage of women needed oxytocin for augmentation both in group I and group II but difference did not reach statistical significance. Our study found that women who were admitted in their latent phase of labor have increased obstetric interventions compared to those in active phase of labor, the findings which are similar to the previous studies done by Cheyne H. et al [7] and Bailit JL et al [8] . Holmes et al [9] found greater frequencies of use of oxytocin and epidural analgesia by women presenting earlier in labour compared to women in active labour.…”
Section: Discussionsupporting
confidence: 92%
“…The present study shows a higher percentage of women needed oxytocin for augmentation both in group I and group II but difference did not reach statistical significance. Our study found that women who were admitted in their latent phase of labor have increased obstetric interventions compared to those in active phase of labor, the findings which are similar to the previous studies done by Cheyne H. et al [7] and Bailit JL et al [8] . Holmes et al [9] found greater frequencies of use of oxytocin and epidural analgesia by women presenting earlier in labour compared to women in active labour.…”
Section: Discussionsupporting
confidence: 92%
“…The process of designing and evaluating the algorithm discussed here indicated that the algorithm could be used consistently by midwives, and was valid, acceptable and easy to complete (Cheyne et al, 2008a, b). The trial results indicated that it did have some effect on midwives' judgements; women in the intervention group who were assessed with the aid of the algorithm in the early stages of labour were significantly more likely to be sent home (Cheyne et al, 2008b). However, these women were also likely to return immediately, creating a 'revolving door' effect, with very little impact on subsequent interventions that they may have received.…”
Section: Implications Of the Study For Our Understanding Of The Diagnmentioning
confidence: 99%
“…More women in the units where midwives were using the algorithm were discharged home following their first visit to the labour ward; however, women quickly returned to the hospital and there was no difference in the overall amount of time that women actually spent in the labour ward. There was no difference in National Health Service (NHS) costs but because women in the experimental group were higher likely to have multiple visits to the labour ward, they incurred higher travel costs as a result of the study intervention (Cheyne et al, 2008b).…”
Section: Phase III or Main Trialmentioning
confidence: 99%
“…The five remaining studies were trials of interventions aimed at improving practices among midwives [21] and primary care physicians [22,23,25,28]. All studies were conducted in highincome countries.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…The four data sets that included five time points in one or both periods were from the studies by Flottorp et al [22], Kerse et al [26], and Cheyne et al [21]. Not surprisingly, the effect estimates based on ITS analyses of such few data points were imprecise (ie, wide 95% CIs, see Fig.…”
Section: Main Findingsmentioning
confidence: 99%